Pengaruh Aktifitas Fisik terhadap Kejadian Penyakit Tidak Menular pada Lansia - Ulfatul Latifah; Iroma Maulidah; Ardhi Henda Karmandika (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
The morbidity rate for the elderly is the proportion of the elderly population who experience health problems that interfere with their daily activities during the past month. According to the 2014 Susenas, the morbidity rate for the elderly population was 25.05%, meaning that out of every 100 elderly people, 25 of them were sick. In Tegal City, the prevalence of non-communicable diseases has a tendency to increase from year to year, this is due to the epidemiological transition, demographic transition and lifestyle transition. This study aims to determine the relationship between physical activity and the incidence of non-communicable diseases in the elderly in Tegal City. This type of analytic observational research uses a cross-sectional design, with a quantitative approach. The population in this study were elderly aged over ≥ 46 years who were in the Tegal City Region. The analytical test used is the chis square test which aims to determine the relationship between physical activity and the occurrence of non-communicable diseases. Data collection was carried out through interviews and filling out questionnaires on the elderly with a sample of 50 people. The results showed that there was a relationship between physical activity and the incidence of non-communicable diseases. The incidence of non-communicable diseases in the elderly can be caused by the high prevalence of risk factors such as lack of physical activity. It is hoped that health workers